2010
DOI: 10.1007/978-3-642-10286-8_13
|View full text |Cite
|
Sign up to set email alerts
|

Role of CD14 in Lung Inflammation and Infection

Abstract: This article is one of ten reviews selected from the Yearbook of Intensive Care and Emergency Medicine 2010 (Springer Verlag) and co-published as a series in Critical Care. Other articles in the series can be found online at http://ccforum/series/yearbook. Further information about the Yearbook of Intensive Care and Emergency Medicine is available from http://www.springer.com/series/2855.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 51 publications
(83 reference statements)
0
23
0
Order By: Relevance
“…This result, however, is in contrast with the findings on the effects of endotoxin exposure. One reason may be that the activation of the inflammatory cascade within the cell depends on the binding of LPS to CD14/TLR4 and it is influenced by several factors such as the type of LPS, the presence of LPS‐binding proteins and the type of surfactant proteins in the lung . This may result in either a beneficial effect to the host by releasing adequate inflammatory response to eradicate the microbes or a detrimental by producing excessive inflammation resulting in severe allergies .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result, however, is in contrast with the findings on the effects of endotoxin exposure. One reason may be that the activation of the inflammatory cascade within the cell depends on the binding of LPS to CD14/TLR4 and it is influenced by several factors such as the type of LPS, the presence of LPS‐binding proteins and the type of surfactant proteins in the lung . This may result in either a beneficial effect to the host by releasing adequate inflammatory response to eradicate the microbes or a detrimental by producing excessive inflammation resulting in severe allergies .…”
Section: Discussionmentioning
confidence: 99%
“…One reason may be that the activation of the inflammatory cascade within the cell depends on the binding of LPS to CD14/TLR4 and it is influenced by several factors such as the type of LPS, the presence of LPS‐binding proteins and the type of surfactant proteins in the lung . This may result in either a beneficial effect to the host by releasing adequate inflammatory response to eradicate the microbes or a detrimental by producing excessive inflammation resulting in severe allergies . Pets also interact with environmental micro‐organisms and may transport these micro‐organisms into dwellings when allowed indoors, particularly into bedrooms, thereby exposing their owners to larger but less specific exposures.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on biomarkers have demonstrated that specific biomarkers were associated with increased disease severity and poorer clinical outcomes in patients with ALI/ARDS [19,20]. sCD14, a new infection-related biomarker, is present in the circulation and other body fluids, and levels of sCD14 in plasma increase during inflammation and infection [21]. Martin et al [22] found that sCD14 levels were markedly increased in bronchoalveolar lavage (BAL) fluid from patients with ARDS, and concluded that sCD14 contributed to the inflammatory process in the lung.…”
Section: Discussionmentioning
confidence: 99%
“…It could be assumed that CD14 has limited opportunities to interact in the inflammatory host response as CD14 lacks a transmembrane domain and therefore the potential to initiate intracellular-signalling by itself (55). It is however known that CD14 acts as a pattern recognition receptor and is one of the main players involved in the signalling pathway of LPS via the TLR4/MD2 receptor complex.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that CD14 contributes to amplified response of other TLRs, than TLR4, e.g. TLR2 (55,56). The level of sCD14 increases in plasma during infection and inflammation and are elevated in BAL fluid from smokers.…”
Section: Cd14mentioning
confidence: 99%